Sodium and Other Inorganic Growth Requirements of Bacteroides amylophilus - Caldwell, Daniel R. (1973)
Bacteroides amylophilus has growth requirements for Na(+), PO(4)(3−), K(+), and small quantities of Mg(2+). No requirement could be shown for Ca(2+) in media previously found growth-yield-limiting for Bacteroides succinogenes. Deletion of Co(2+), Mn(2+), Cl(−), or SO(4)(2−) did not affect growth. Quantitative studies indicate that Na(+), K(+), and PO(4)(3−) have differing effects on the growth of B. amylophilus. A concentration of sodium and potassium ions affects both growth rate and growth yield, whereas a phosphate concentration markedly affects growth yield, but affects growth rate only slightly, if at all. The sodium requirement of B. amylophilus is absolute. It cannot be replaced by K(+), Li(+), Rb(+), or Cs(+). The latter three monovalent cations are toxic to B. amylophilus if supplied to the organism at Na(+)-replacing concentrations. K(+) is inactive at similar concentrations. The K(+) requirement of B. amylophilus may be satisfied by Rb(+). The concentration of Na(+) required by B. amylophilus for abundant growth suggests that B. amylophilus should be considered a slightly halophilic organism. The results suggest that Na(+) may be a more frequent requirement among terrestial bacteria obtained from relatively low-salt environments than has been previously believed.